DEVELOPING MULTIMODAL ENGLISH LEARNING MEDIA FOR RURAL JUNIOR HIGH SCHOOL STUDENTS USING ANIMAKER - Nurul Afiyattena; Siti Hanna Sumedi; Nadilla Dwi Haerani (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2026)
This study purposes to design and develop multimodal English learning media using Animaker for junior high school students at a rural area in Lebak regency, Banten province. In this study, Design-Based Research (DBR) method was applied, the population of the study was 121, with 32 junior high school students participating. The data were obtained from questionnaires, interviews, document analysis, and focus group discussions (FGD). Quantitative data were analyzed using descriptive statistics, whereeas qualitative data were interpreted thematically. The finding revealed that students were excited to have a multimodal English learning media, it showed from their positive responses as 89.07%. In addition to the result of experts’ judgment who gave 87.16 % for the appropriateness of this multimodal English learning media to be used by students and teacher. Thus, the findings of this study highlight that English multimodal media can foster learning engagement, and excitement especially for students in underdeveloped area, considering the suitability and appropriateness of the material with the needs and local environment of students. Hence, it is suggested for further development and teacher training in the use of digital multimodal literacies.